2016
DOI: 10.1139/cjps-2016-0140
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for assessing drought tolerance in a segregating population of flax (Linum usitatissimum L.)

Abstract: Using plant genotypes adaptable to water-deficit stress is an optimal strategy in sustainable agriculture. This study was conducted to assess the selection criteria for identifying high yielding-drought tolerant F 2 -derived F 3 flax families from a cross between Iranian genotype KO37 and the Canadian genotype SP1066. One hundred and nineteen F 2:3 were evaluated under drought stress and non-stress conditions using an 11*11 lattice design with three replications. Sixteen drought tolerance indices adjusted base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Higher water stress tolerance in brown-seeded families may be attributed to secondary metabolites biosynthesis such as lignans and tannins in the seed coat. Similar to this interpretation, Asgarinia et al 27 , Pizzi and Cameron 29 and Hassanpour et al 30 reported that brown-seeded genotypes were more resistant to drought stress due to the higher hardiness of seed coat, the presence of secondary metabolites, tannins, and their antioxidant properties compared to yellow-seeded genotypes. Tannins present in the brown seed coat can also influence seed vigor 34 .…”
Section: Discussionmentioning
confidence: 57%
“…Higher water stress tolerance in brown-seeded families may be attributed to secondary metabolites biosynthesis such as lignans and tannins in the seed coat. Similar to this interpretation, Asgarinia et al 27 , Pizzi and Cameron 29 and Hassanpour et al 30 reported that brown-seeded genotypes were more resistant to drought stress due to the higher hardiness of seed coat, the presence of secondary metabolites, tannins, and their antioxidant properties compared to yellow-seeded genotypes. Tannins present in the brown seed coat can also influence seed vigor 34 .…”
Section: Discussionmentioning
confidence: 57%
“…These findings were like Paul et al (2017), who also observed that the PCV values were greater than the GCV values for all the traits studied. Previous studies by Basavaraj et al (2011) and Asgarinia et al (2014) stated high PCV and GCV for number of capsules per plant, number of seeds per capsule and yield per plant. Hence, selection for number of primary branches, number of capsules per plant and seed yield per plant are influenced by environmental effects from difference between the PCV and GCV was high could be due to the heterogeneity in soil fertility status and other unpredictable factors (Reddy et al, 2012).…”
Section: Coefficient Of Variation Phenotypic and Genotypic (Pcv And Gcv)mentioning
confidence: 82%
“…The climate chamber experiments were conducted at the Julius Kühn Institute (JKI), Federal Research Centre for Cultivated Plants, Institute for Resistance Research and Stress Tolerance, Quedlinburg, Germany with 196 accessions. These were selected by the least-square means (lsmeans) of grain biomass of 2016 drought stress locations and 2017 Holetta (control treatment) by three drought indices namely, drought susceptibility index, tolerance index, and yield reduction index, as described by Asgarinia et al (2017). The results were used to cluster the 260 accessions into seven clusters, using SAS 'proc cluster' procedure (SAS Institute 2019), and 75.4% of accessions were randomly selected from each cluster to accommodate a set of 196 accessions used for climate chamber experiments.…”
Section: Climate Chamber Experimentsmentioning
confidence: 99%